Using a MG-M imagery intervention to enhance the sport competence of young special Olympics athletes - Catenacci, K. L.; Harris, B. S.; Langdon, J. L.; Scott, M. K.; Czech, D. R. (Journal of Imagery Research in Sport and Physical Activity, 2015)
Opportunities for athletes with an intellectual disability (ID) to participate in sport are limited by physical and psychosocial barriers. Sport psychology interventions may be able to address these barriers, namely the lack of sport competence that athletes with an ID experience. This study sought to enhance sport competence among athletes with an ID using personalized motivational general-mastery (MG-M) imagery scripts. The six-week study assessed the imagery use, imagery ability, and sport competence of five Special Olympians (Mage=11.40) who had ID`s including autism, a mild intellectual disability, and a moderate intellectual disability. Three of five participants demonstrated improvements in sport competence through the intervention, with two of those three maintaining these changes upon withdrawal of the intervention. Effect sizes suggested that scores became more stable during the intervention for three of five participants. Implications of the current study emphasize the feasibility of conducting research with this special population of athletes. Additionally, this study identifies the relevant modifications for mental skills training with individuals who have an ID. Results suggest that imagery use, ability, and sport competence can be improved with individualized imagery training among athletes with an ID.